Investigating English Language Teachers’ Motivation in Private Institutes in Iran - Ehsani, Maryam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Motivation is the main drive behind any course of action which aims success. Considering the fact that teachers are the main agents for the success of an institution, the issue of teachers’ motivation has always attracted great attention among researchers in the field of education. There have been a number of studies conducted in the context of Iran, investigating the teacher motivation and job satisfaction from various perspectives. However, there seem to be no studies conducted on the motivation of English language teachers teaching in private institutes in different cities in Iran. To address this gap, the present study has been conducted in six different private institutes in four different cities in Iran (namely, Tehran, Isfahan, Mashhad and Yazd) to investigate the perceptions of the Iranian English language teachers in those institutes regarding teaching, self-efficacy, their teaching context and colleagues. The study also aims to elicit how the participants perceive the motivation-related factors in their job. The study followed both quantitative and qualitative methodology which means a mixed-method. The data were collected from 150 English language teachers working in these six institutes. In addition, semi-structured interviews were conducted with 10 volunteers. The data analysis revealed a general satisfaction of the English language teachers in private institutes of Iran regarding their job as well as their self-efficacy. Considering the factors of English teachers’ motivation, the results highlighted two main sub-themes: intrinsic and extrinsic types of motivating or demotivating factors. The results indicated that Iranian English language teachers’ motivation or demotivation was mostly influenced by extrinsic factors. To increase the motivation level of English language teachers in the context of Iran, this study has a number of implications. It is recommended that managers, as leaders of their institutes, need to be informed about the importance of their role and influence on teachers’ motivation. For this purpose, some leadership courses can be designed, and managers, as leaders of their institute, can be encouraged to participate in these training programs. The participating English language teachers in the study criticize the lack of opportunities for their participation in the decision-making stages of teaching- learning process, and this does not contribute to their motivation. To increase their motivation, weekly or monthly meetings can be organized in which teachers share their ideas with colleagues. This kind of meetings may also help teachers to meet their colleagues, who are another factor of their motivation or demotivation. This study also highlighted the importance of students’ role on teachers’ motivation. Equipping institutes by modern audiovisuals and attractive learning assist tools, which was the mentioned factors for teachers, will not only keep the students motivated but also increase teachers’ motivation. Also, involving teachers and students in supporting programs or conferences may help both to develop their motivation. Finally, financial incentives, good salaries, and regular payment are reported to be important factors in increasing English language teachers’ motivation in private institutes in Iran.

ÖZ: Motivasyon, başarıyı hedefleyen her türlü eylemin ardındaki ana itici güçtür. Öğretmenlerin bir kurumun başarısı için ana etken olduğu düşünüldüğünde, öğretmenlerin motivasyonu konusu eğitim alanındaki araştırmacılar arasında her zaman büyük ilgi görmüştür. İran bağlamında öğretmen motivasyonunu ve iş doyumunu çeşitli açılardan araştıran bir dizi çalışma yapılmıştır. Ancak, İran'ın farklı şehirlerinde özel kurumlarda öğretmenlik yapan İngilizce öğretmenlerinin motivasyonu konusunda herhangi bir çalışma yapılmamıştır. Bu boşluğa değinmek için, bu çalışma İran'daki dört farklı şehirde (Tahran, İsfahan, Meşhed ve Yezd) altı farklı özel kurumda, bu kurumlardaki İranlı İngilizce öğretmenlerinin öğretim, özyeterlik ve öğretim bağlamı ve çalışma arkadaşları ile ilgili algılarını araştırmak amacıyla yapılmıştır. Çalışma aynı zamanda katılımcıların çalıştıkları kurumda motivasyonla ilgili faktörleri nasıl algıladıklarını ortaya çıkarmayı amaçlamaktadır. Çalışma, karma yöntem yaklaşımını izlemiştir; bu kapsamda bu altı kurumda çalışan 150 İngilizce öğretmeninden hem nicel hem de nitel veri toplanmıştır. Ayrıca 10 gönüllü ile yarı yapılandırılmış görüşmeler yapılmıştır. Veri analizi, İran'da özel kurumlardaki İngilizce öğretmenlerinin işlerinin yanı sıra özyeterliklerinden genel olarak memnuniyet duyduklarını ortaya koymuştur. İngilizce öğretmenlerinin motivasyon faktörleri göz önüne alındığında, sonuçlar iki ana alt tema etrafında ele alınabilir: içsel ve dışsal tipte motive edici veya demotive edici faktörler. Elde edilen sonuçlar, İranlı İngilizce öğretmenlerinin motivasyon varlığının veya motivasyon eksikliğinin çoğunlukla dışsal faktörlerden etkilendiğini göstermiştir. Bu çalışmanın sonuçlarına dayanarak, İran bağlamında İngilizce öğretmenlerinin motivasyon düzeyini artırmak için bir dizi öneriler yapılabilir. İlk olarak, özel kurumların liderleri konumundaki yöneticilerin, kurumsal rollerinin önemi ve öğretmenlerin motivasyonu üzerindeki etkisi konusunda bilgilendirilmeleri önerilir.Bu amaçla, bazı liderlik kursları tasarlanabilir ve kurum yöneticileri bu eğitim programlarına katılmaya teşvik edilebilir. Ayrıca, çalışmaya katılan bazı İngilizce öğretmenleri, çalıştıkları kurumda öğretme-öğrenme sürecinin karar verme aşamalarına bizzat katılmarı konusunda fırsat olmamasını eleştirmiştir. Bu çerçevede, öğretmenlerin fikirlerini meslektaşlarıyla paylaşacakları haftalık veya aylık toplantılar düzenlenebilir. Bu tür toplantılar, öğretmenlerin motivasyonlarının artmasına neden olabileceği gibi, motivasyonlarının artmasında bir başka faktör olan meslektaşlarıyla daha yakından tanışmalarına ve işbirliği yapmalarına da yardımcı olabilir. Çalışmada, öğrencilerin de öğretmenlerin motivasyonu üzerindeki rolünün önemi vurgulanmıştır. Söz konusu kurumların modern görsel-işitseller ve teknolojik araçlar ile donatılması, sadece öğrencileri motive etmekle kalmayacak, aynı zamanda öğretmenlerin de motivasyonunu artıracaktır. Ayrıca, öğretmenleri hizmetiçi eğitim programlarına veya konferanslara dahil etmek motivasyonlarının gelişmesine yardımcı olabilir. Son olarak, çalışmada finansal teşviklerin, iyi maaşların ve düzenli ödemenin, çalışmaya katılan İngilizce öğretmenlerinin motivasyonlarını artırmada önemli faktörler olduğu vurgulanmıştır.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2020. Supervisor: Prof. Dr. Ülker Vancı Osam.
Keywords: English Language Teaching (ELT); English Language--Study and Teaching; English Teaching--Private Institutes--Iran; Motivation; job satisfaction; self-efficacy; extrinsic factors; intrinsic factors; EFL teachers; private institutes; Iran